ANALISIS INTENSITAS KERUSAKAN MAHONI (Swietenia mahagoni) AKIBAT SERANGAN HAMA DAN PENYAKIT TUMBUHAN - Muhammad Ramadhan; Dina Naemah; Ahmad Yamani (Jurnal Sylva Scienteae, 2020)
Mahoni (Swietenia mahagoni) is a type of tree that is widely used as a greening plant and also used as a pollution cleaning plant because it is able to absorb pollutants in the air. In order for this tree to be able to work well, it should be noted for its health. This research on mahoni aims to analyze the damage from mahoni trees and calculate the percentage of mahoni tree damage due to pests and plant diseases carried out in permanent nursery management centers for watersheds and protected forests for three months. Mahoni trees used as the object of research amounted to 81 trees while the tools used were binoculars and writing instruments.The method used in this research is to use Environmental Monitoring and Assessment Program (EMAP) method. The results obtained from this research are based on observations in the field, it was found that there were four parts of the tree that were damaged which thas was lower trunk, upper trunk, branches, and leaves.Based on observations also found there are four different types of damage suffered by mahoni which that was wounds, broken and dead, damaged leaves, and leaf discoloration. Based on these results, the most damaged part of the tree was the branch and the least was the lower trunk. Other results show the type of damage most suffered by mahoni was broken and dead while the least was wounds. There were 126 cases of damage suffered by mahoni in which as many as 15 cases were caused by pests and 111 cases the rets were caused by diseases. Based on these data, it can be concluded that mahoni damage caused by disease was higher than that caused by pests.Keywords: Mahoni; Pest; Disease